New 1E,1′E-hydrazine-bis(phenoxy-1,2,3-triazol-acetamide) derivatives as potent inhibitors against acetylcholinesterase, butyrylcholinesterase, and α-glucosidase - Kermaninia, Shahab; Mohammadi-Khanaposhtani, Maryam; Senol, Halil; Khajeh Mohammadilar, Fatemeh Sadat; Dastyafteh, Navid; Moradkhani, Fatemeh; Saeedi, Saeedeh; Taslimi, Parham; Taslimi, Parham (Royal Soc Chemistry, 2025)
In this study, novel 1E,1 ' E-hydrazine-bis(phenoxy-1,2,3-triazol-acetamide) derivatives 10a-n were synthesized, and because of their structural features, they were evaluated against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and alpha-glucosidase. AChE and BChE are two important targets in the treatment of Alzheimer's disease (AD), and alpha-glucosidase is a carbohydrate-hydrolyzing enzyme with therapeutic importance in diabetes. Furthermore, cell studies were performed on the title compounds against SH-SY5Y neuroblastoma cells as a cancer cell line and HEK293 cells as a normal cell line. In vitro enzymatic evaluations demonstrated that these new compounds were active against the studied enzymes in comparison to standard inhibitors. In this regard, all the synthesized compounds were more potent than the standard inhibitors tacrine and donepezil against BChE, and most of these compounds were more potent than tacrine against AChE. Moreover, most of the target synthesized compounds were more potent than the standard inhibitor acarbose against alpha-glucosidase. The most potent compound against AChE and BChE was the 2,4-dichloro derivative 10k, and the most potent compound against alpha-glucosidase was the 2-chloro derivative 10h. Moreover, in vitro cell studies demonstrated that compounds 10k and 10h with a selectivity index of >10 demonstrated more cytotoxic effects on the cancer cell line SH-SY5Y than on the normal cell line HEK293. A docking study showed that the latter compounds attached to the active sites of the target enzymes with binding energies more favorable than those of the selected standard inhibitors. Furthermore, docking studies demonstrated that compound 10k interacted with both the catalytic and peripheral anionic sites of AChE and BChE. This property led to the better efficacy of the compound in the treatment of AD.
Keywords: [No Keywords]